The Influence of Father’s Involvement on the Level of Marriage Satisfaction of Couples in Kenya - Maina, Stella; Lucy Njiru, Lucy; Kitonga, Daniel (Journal of Psychology, Guidance and Counseling, 2021)
The purpose of this study was to establish the extent to which a father’s involvement affects the level of marriage satisfaction of couples in Westlands Constituency, Nairobi County. The study was based on the Attachment Theory as well as the Theory of Psychoanalysis. This study employed the survey research design among married individuals both male and female from Westlands Constituency in Nairobi County who were above eighteen years of age. The data was collected using questionnaires from 384 participants using simple random sampling. The completed questionnaires were then analysed by the use of the Statistical Package for Social Sciences (SPSS) whereby the descriptive statistics were analysed using frequencies and percentages while the inferential statistics were analysed by use of the Pearson correlation coefficient. The study concluded that father involvement has a statistically significant negative effect on marriage relationship outcomes of individuals. With a father involvement level that is low, there is a likelihood that the marriage relationship of an individual would be negatively affected. The study recommended that in case of separation, the parents should consider active co-parenting which will ensure that fathers are actively engaged in the lives of their children so that the children do not have feelings of abandonment. The parents can also consider joining parenting support groups
Keywords: father involvement; marriage satisfaction; couples; psychoanalysis; attachment.